A Review of Active Yaw Control System for Vehicle Handling and Stability Enhancement. (12th June 2014) - Aripin, M. K.; Md Sam, Yahaya; Danapalasingam, Kumeresan A.; Peng, Kemao; Hamzah, N.; Ismail, M. F.
Abstract : Yaw stability control system plays a significant role in vehicle lateral dynamics in order to improve the vehicle handling and stability performances. However, not many researches have been focused on the transient performances improvement of vehicle yaw rate and sideslip tracking control. This paper reviews the vital elements for control system design of an active yaw stability control system; the vehicle dynamic models, control objectives, active chassis control, and control strategies with the focus on identifying suitable criteria for improved transient performances. Each element is discussed and compared in terms of their underlying theory, strengths, weaknesses, and applicability. Based on this, we conclude that the sliding mode control with nonlinear sliding surface based on composite nonlinear feedback is a potential control strategy for improving the transient performances of yaw rate and sideslip tracking control.